Silagem de colostro bovino: propriedades e potencialidades de usos - Saalfeld, Mara Helena (2013)
Colostrum is considered essential for newborns as a nutritional source and transfer for passive immunity. The production of colostrum above the calf intake capacity enables using the surplus as a milk replacer. One way of using it is through the anaerobic fermentation commonly called as colostrum silage. This food provides adequate weight gain to the animals; however, there is no data concerning the result of anaerobic fermentation on its elements. The aim of this study was to assess the physic-chemical, microbiological and immunological characteristics of the colostrum silage and its usage as nutritional supplement in animal feeding and its usage in the production of food for human usage. The centesimal assessment demonstrated that colostrum has nutrients in bigger amounts than the ones found in milk and that the colostrum silage kept the nutrients found in colostrum in natura, mainly the proteins (14,24%), dry matter (17,54%) and fat (5,55%), with the exception of lactose which, 30 days after fermentation was not detected anymore. It was noticed that the pH values decreased while there was an increase of lactic acid concentrations. Animals fed with colostrum silage had a weight gain at weaning of 0.7 above (p<0.05) the control animals (food with milk) which presented weight gains of 0.6 kg/day. The microbiological assessment showed that 21 days after fermentation the pathogenic bacteriae tested were not detected anymore, while there were still lactic acid bacteriae identified through sequencing the 16S rDNA as Lactobacillus (75%) and Enterococcus (25%). Identified as Lactobacillus (75%) (L. casei, L. brevis, L. rennanqily, L. crustorum) and Enterococcus (25%) (E. durans, E. faecium E. faecalis and E. mundyii). The immunoglobulins assessment in colostrum silage was carried out through the Immuno enzymatic method (ELISA), in which it was proved that after 12 months of storage, the colostrums silage kept feasible immunoglobulins and these were transmitted to newborns in the same proportion as the colostrum in natura. It was possible to elaborate foods such as dairy beverage and butter from the colostrum silage keeping the nutritional characteristics and microbiota containing lactic acid bacteria. The carrying out of sensory analysis reached an acceptance of 85% and purchasing intention from the assessors. Thus, it can be concluded that colostrums silage is a food of high nutritional value, microbiologically innocuous food, with immunological capability, and that it can be used in animal feeding with the need of proper legislation to enable its usability as human food.